SURVEY KEPUASAN PELANGGAN PDAM KABUPATEN KLATEN - Nursito, Sarwono; Nugroho, Arif Julianto Sri; Haris, Abdul (Widya Dharma Journal of Business - WIJoB, 2022)
This study aims to determine the Community Satisfaction Index (IKM) of public services provided by PDAM Klaten Regency. The method used is a survey method using a questionnaire to collect research data. Respondents who were the sample of the study were 404 customers. The sampling technique used is cluster sampling, where the population is divided based on the service area and stratified sampling, where the population is divided based on the customer class. While the data analysis uses the Community Satisfaction Index (IKM) analysis, both as a whole and per service element. The result of the analysis shows that the overall IKM value is 76.18, which is in the good category.